Initial Results from Mobile Low‐Dose Computerized Tomographic Lung Cancer Screening Unit: Improved Outcomes for Underserved Populations. (26th November 2019) - Raghavan, Derek; Wheeler, Mellisa; Doege, Darcy; Doty, John D.; Levy, Henri; Dungan, Kia A.; Davis, Lauren M.; Robinson, James M.; Kim, Edward S.; Mileham, Kathryn F.; Oliver, James; Carrizosa, Daniel
Abstract: Introduction: The National Lung Screening Trial (NLST) demonstrated that screening high‐risk patients with low‐dose computed tomography (CT) of the chest reduces lung cancer mortality compared with screening with chest x‐ray. Uninsured and Medicaid patients usually lack access to this hospital‐based screening test because of geographic and socioeconomic factors. We hypothesized that a mobile screening unit would improve access and confer the benefits demonstrated by the NLST to this underserved group, which is most at risk of lung cancer deaths. Patients and Methods: We created a mobile unit by building a Samsung BodyTom portable 32‐slice low‐dose CT scanner into a 35‐foot coach; it delivers high‐quality images for both soft tissue and bone and includes a waiting area and high‐speed wireless internet connection for fast image transfer. The unit was extensively tested to show robustness and stability of mobile equipment. This project was designed to screen uninsured and underinsured patients, otherwise with eligibility criteria identical to that of the National Lung Screening Trial, with the only difference being exclusion of patients eligible for Medicare (which provides financial coverage for CT‐based lung cancer screening). Results: We screened 550 patients (20% black, 3% Hispanic, 70% rural) with a male‐to‐female ratio of 1.1:1, median age 61 years (range, 55–64), and found 12 lung cancers at initial screen (2.2%), including 6 at stage I–II (58% of total lung cancers early stage) and 38 Lung‐RADS 4 (highly suspicious) lesions that are being followed closely. Incidental findings included nonlung cancers and coronary artery disease. Discussion: In this initial pilot study, using the first mobile low‐dose whole body CT screening unit in the U.S., the initial cancer detection rate is comparable to that reported in the NLST, despite excluding patients over the age of 64 years who have Medicare coverage, but with marked improvement of screening rates specifically in underserved sociodemographic, racial, and ethnic groups and with better outcomes than conventionally found in the underserved and at lower cost per case. Implications for Practice: This study shows clearly that a mobile low‐dose CT scanning unit allows effective lung cancer screening for underserved populations, such as impoverished African Americans, Hispanics, Native Americans, or isolated rural groups, and has a pick‐up rate of 1% for early stage disease. If confirmed in a planned randomized trial, this will be policy changing, as these groups usually present with advanced disease; this approach will produce better survival data at lower cost per case. Abstract : The BodyTom CT is the first mobile screening unit in the U.S., designed to improve access to lung cancer screening for underserved patient groups. This article reports results of the initial pilot study using this first‐of‐its‐kind mobile low‐dose whole body CT screening unit. Twelve cases of lung cancer were found in 550 smokers (including 6 early stage).